Healthcare information technology (IT) and management systems Part 1 – European experiences in electronic patient health account - Wdowiak, Leszek; Horoch, Andrzej; Bojar, Iwona; Jarosz, Mirosław J. (Polish Journal of Public Health, 2009)
IT systems applied to rationalise the functioning of healthcare are subject of interest to many European countries. One of the subsystems realized under information system is Electronic Patient Health Account designed for the customers to whom the medical records are provided in the form of medical documents and additional functions like customer’s personal data handling, fi les concerning appointments, referrals, prescriptions, data concerning prophylactics, cost of treatment, etc. The aim of the research is to analyse the existing and planned technical-technological and organizational-legislative achievements applied in systems with common charakter in selected commercial systems in health care that function in Europe, with regard to identifi cation and specifi cation of good practices, defi ning of cooperation principles, identifi cation and description of functional and non-functional requirements and making use of electronic signature. The study presents systems applied is Denmark, Spain, Czech Republic, Germany and Finland. Functional ranges of electronic patient records in various countries are similar and are based on building a medical case history to make it accessible both for the patient and the professional after informed consent expressed by the patient. The analysis of the future plans in individual countries suggest that all of the solutions focus on a very common aim of functionality